It's not the end of the world - Blume, Judy. (New York : Bantam Doubleday Dell Books for Young Readers, 1986)
When her parents divorce, a sixth grader struggles to understand that sometimes people are unable to live together.
"A Yearling book.".
Elem. School Library Collection.
School Library Journal.
Wilson's Children.
3.9
3-6
Keywords: Divorce -- Fiction; Divorce -- Fiction